Wedge Mode Propagation Characteristics of Triangular–shaped Surface Plasmon Waveguide - Chinh, Nguyen Van; Huong, Nguyen Thanh; Hoang, Chu Manh (VNU Journal of Science: Mathematics - Physics; Vol 32 No 3DO - 10.25073/2588-1124/vnumap.4051, 2016)
Abstract: In this paper, we investigate wedge mode propagation characteristics of a triangular-shaped surface plasmon waveguide. This structure consists of a thin metal layer deposited onto the surface of a triangular–shaped silicon waveguide which could be fabricated on a silicon–on–insulator wafer by wet–bulk micromachining. These elements are embedded in a dielectric medium (such as air) to form metal–dielectric interface and the surface plasmon wave propagates at the wedge of metal layer. The influence of structural parameters such as metal layer, height of silicon waveguide and effect of fabrication on the wedge mode propagation characteristics of the waveguide is analyzed by using numerical simulation. Keywords: V–shaped waveguide, Surface plasmon polariton, plasmonic waveguide.